2003
DOI: 10.1353/jae.2003.0022
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Understanding as Informed Experience: The Role of Knowledge in Our Art Viewing Experiences

Abstract: Richard Lachapelle is Associate Professor on the Faculty of Fine Arts at Concordia University, Montreal, Quebec. His recent publications include several chapters in art education books as well as articles in the Canadian Review of Art Education and Studies in Art Education. Deborah Murray (M.A., Educational Technology) and Sandy Neim (M.A., Art Education) are both recent graduates of Concordia University's School of Graduate Studies.Thinking calls for images, and images contain thought. Therefore, the visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Taken as a whole, this literature on "verbal overshadowing" serves as a forceful reminder that there are modes of perception not only not aided, but actually harmed by verbal description. Exceptions include studies about the role of information in the visual arts, where studies have shown that information can enhance satisfaction and understanding in viewing art (Lachapelle, Murray, & Neim, 2003;Temme & Elbert, 1992). Since musical listening has often been thought about as nonconceptual in important ways (Abbate, 2004;DeBellis, 1995), it might seem particularly susceptible to verbal overshadowing.…”
mentioning
confidence: 99%
“…Taken as a whole, this literature on "verbal overshadowing" serves as a forceful reminder that there are modes of perception not only not aided, but actually harmed by verbal description. Exceptions include studies about the role of information in the visual arts, where studies have shown that information can enhance satisfaction and understanding in viewing art (Lachapelle, Murray, & Neim, 2003;Temme & Elbert, 1992). Since musical listening has often been thought about as nonconceptual in important ways (Abbate, 2004;DeBellis, 1995), it might seem particularly susceptible to verbal overshadowing.…”
mentioning
confidence: 99%
“…The aesthetic experience provides the basis for symbolism and expression, and is connected with the basic facets of a person's communicative behaviour (Johnson, 2007). In conclusion, aesthetic experience is the symbolic representation of reality and contributes to a direct grasp of the aesthetic and expressive characteristics of objects (Bresler, 2007), about which the subject constructs new knowledge (Lachapelle, Murray, & Neim, 2003).…”
Section: Aesthetic Experiencementioning
confidence: 99%
“…As noted, it is important for museums and exhibition centres to provide information that helps place "art in the context of other expressions of human initiative," as advocated by the anthropologist Geertz (1983, p. 119), such that visitors may have experiences that are both culturally responsible and personally significant (Barrett, 2000;Hubard, 2007;Lachapelle, Murray, & Neim, 2003;Lankford, 2002;Meszaros, 2007aMeszaros, , 2007b.…”
Section: Rigorous Informationmentioning
confidence: 99%
“…Educators such as Barrett (2000), Lachapelle et al (2003), Meszaros (2007aMeszaros ( , 1007b, Hubard (2007) and Lankford (2002) inspire us in this regard when they suggest that the dialogue between the meanings provided by visitors, those belonging to other cultural traditions and those of the institution itself is what makes it possible to construct richer and more meaningful relationships with art. Lankford puts it this way:…”
Section: Giving the Viewer A Voice In The Construction Of Meaningmentioning
confidence: 99%
See 1 more Smart Citation